Impelentasi User Experience Questionnaire Untuk Analisa Kuliatas Online Travel Agent Terhadap Pengalaman Pengguna - Hary Juni Kurniawan; Eko Setia Budi (STMIK Budi Darma, 2024)
The development of advanced technology in Indonesia today allows various activities to be carried out digitally, including in the tourism and travel sector. Users often choose Online Travel Agent (OTA) applications that are easy to use in planning their trips, currently there are many Online OTA applications but the most commonly used are Traveloka, Tiket.com, and Agoda. These applications have the same characteristics, namely providing online ticketing, reservation, and accommodation services. This study aims to compare the three OTA applications using the User Experience Questionnaire (UEQ) method to measure application quality based on user experience assessed through six scales. Data collection was conducted using Google Forms distributed to users of Traveloka, Tiket.com, and Agoda applications, and obtained 214 respondents, consisting of 105 Traveloka user respondents, 66 Tiket.com users, and 43 Agoda users. The results of the user experience analysis from the UEQ Questionnaire show a positive impression because all applications get an evaluation with an average value above 0.8 on the six UEQ scales. From the comparison results of the three applications, Agoda is superior on the efficiency scale compared to Traveloka and Tiket.com despite having fewer respondents. This research provides an overview of the quality of user experience on the three OTA applications and can be a reference for application developers to improve the quality of their services.